ModOdor: 3D numerical model for dispersion simulation of gaseous contaminants from waste treatment facilities. (March 2019) - Liu, Yanjun; Zhao, Yan; Lu, Wenjing; Wang, Hongtao; Huang, Qifei
Abstract: Pollution caused by gaseous contaminant from waste treatment facilities, such as wastewater plants, municipal solid waste landfills, transfer stations, has elicited public concern. The potential environmental impacts of gaseous emissions from waste sectors are regulated by legislations in many countries, and dispersion models are powerful tools. Mod eling ofOdor gas air dispersion software (ModOdor), a 3D unsteady-state numerical model, was developed in this study to simulate the dispersion of gaseous contaminants from waste sectors. ModOdor overcomes the limitations of Gaussian and Lagrangian models when applied to unsteady-state, local-scale gaseous dispersion from waste sectors, because it adopts the numerical Eulerian scheme and finite difference method. Particularly, ModOdor can generate potential flow solutions associated with complex topography, process different types of emission sources, simulate spatiotemporal variations in meteorological conditions (wind and dispersion), and implement physical/chemical reactions for tracking the temporal and spatial evolution of plume and managing gaseous pollution from waste sectors. Highlights: ModOdor is a 3D unsteady state numerical model for dispersion from waste sector. ModOdor adopts the numerical Eulerian scheme and finite difference method. Topography, meteorological variance and depletion process could be modeled. Multiple wind field, diffusion coefficients and source typed are realized in ModOdor.